Technique, outcomes, and acute toxicities in adults treated with proton beam craniospinal irradiation. Issue 2 (4th December 2013) - Barney, Christian L.; Brown, Aaron P.; Grosshans, David R.; McAleer, Mary Frances; de Groot, John F.; Puduvalli, Vinay; Tucker, Susan L.; Crawford, Cody N.; Gilbert, Mark R.; Brown, Paul D.; Mahajan, Anita
Abstract: Background: Proton craniospinal irradiation (p-CSI) has been proposed to reduce side effects associated with CSI. We evaluated acute toxicities and preliminary clinical outcomes in a series of adults treated with p-CSI. Methods: We reviewed medical records for 50 patients (aged 16–63 y) with malignancies of varying histologies treated consecutively with vertebral body-sparing p-CSI at MD Anderson Cancer Center from 2007 to 2011. Median CSI and total boost doses were 30.6 and 54 Gy. Forty patients received chemotherapy, varying by histology. Median follow-up was 20.1 months (range, 0.3–59). Results: Median doses to the thyroid gland, pituitary gland, hypothalamus, and cochleae were 0.003 Gy–relative biological effectiveness (RBE; range, 0.001–8.5), 36.1 Gy-RBE (22.5–53.0), 37.1 Gy-RBE (22.3–54.4), and 33.9 Gy-RBE (22.2–52.4), respectively. Median percent weight loss during CSI was 1.6% (range, 10% weight loss to 14% weight gain). Mild nausea/vomiting was common (grade 1 = 46%, grade 2 = 20%); however, only 5 patients experienced grade ≥2 anorexia (weight loss >5% baseline weight). Median percent baseline white blood cells, hemoglobin, and platelets at nadir were 52% (range, 13%–100%), 97% (65%–112%), and 61% (10%–270%), respectively. Four patients developed grade ≥3 cytopenias. Overall and progression-free survival rates were 96% and 82%, respectively, at 2 years and 84% and 68% at 5 years. Conclusions: This large series of patients treated with p-CSI confirms low rates of acute toxicity, consistent with dosimetric models. Vertebral body-sparing p-CSI is feasible and should be considered as a way to reduce acute gastrointestinal and hematologic toxicity in adults requiring CSI.